Acute Kidney Injury in Pediatric Acute Decompensated Heart Failure. Issue 6 (July 2015) - Medar, Shivanand S.; Hsu, Daphne T.; Lamour, Jacqueline M.; Aydin, Scott I.
<x xml:space="preserve">Abstract</x> Objective: Acute kidney injury in adult patients with acute decompensated heart failure is associated with increased mortality. There is limited literature in pediatric patients with acute decompensated heart failure and acute kidney injury. We aim to study acute kidney injury in the pediatric acute decompensated heart failure population and its association with specific outcomes. Design: Retrospective, case-control study. Setting: Cardiac ICU in a children's tertiary care hospital. Patients: Index admissions of patients younger than 21 years with acute decompensated heart failure between January 2008 and December 2012. Interventions: None. Measurements and Main Results: Index admissions of patients younger than 21 years with acute decompensated heart failure between January 2008 and December 2012 were reviewed, and the presence or absence of acute kidney injury at admission was determined based on the Pediatric Risk, Injury, Failure, Loss, End-Stage criteria. Descriptive statistics and multivariate analyses were performed to determine the association between acute kidney injury and a composite outcome of cardiac transplantation and/or mortality. Fifty-seven patients, with median age 12 years (interquartile range, 1.1, 16), were included for study. The median left ventricular ejection fraction was 27% (interquartile range, 18, 48). Twenty-one patients (36%) underwent cardiac transplantation and five patients (8.7%) died. Of the 57 patients, 44 (77%) had evidence of acute kidney injury (41% Risk; 39% Injury; 20% Failure). Of the 44 patients with acute kidney injury, 25 (57%) met the composite outcome, compared with 1 (7%) without acute kidney injury. Multivariate analyses demonstrated that a left ventricular ejection fraction up to 25% was significantly associated with the presence of acute kidney injury (adjusted odds ratio, 12.3; 95% CI, 1.4–109; p = 0.03), and acute kidney injury was significantly associated with the composite outcome (adjusted odds ratio, 19.1; 95% CI, 2.3–160; p < 0.001). Conclusions: Acute kidney injury is common during the initial presentation of pediatric patients with acute decompensated heart failure. A left ventricular ejection fraction up to 25% is associated with acute kidney injury. The presence of acute kidney injury in this population is significantly associated with cardiac transplantation and/or death.